38.2k views
5 votes
Solve for x.x^2 + 6x + 9 = 12x= -3+2V3x = -3+4V3x= -9 + 4V3x=-9 + 2V3

User Andlabs
by
5.5k points

1 Answer

1 vote

1) Solving this quadratic equation by the Resolutive formula, we have:


\begin{gathered} x^2+6x\text{ +9=12} \\ x^2+6x-12+9=0 \\ x^2+6x-4=0 \\ \Delta=b^2-4ac=6^2-4(1)(-4)=36+16=52 \\ x=\frac{-6\pm\sqrt[]{52}}{2} \\ x_1=-3+\sqrt[]{13} \\ x_2=-3-\sqrt[]{13} \\ S=\mleft\lbrace-3-\sqrt[]{13},-3+\sqrt[]{13}\mright\rbrace \end{gathered}

User Lenkite
by
4.7k points